Case: Quality of Studentâs Content Writing Through Implementation of Project Based Learning Model in Biology - Indriani, Anita; Widoretno, Sri; Dwiastuti, Sri (Universitas Ahmad Dahlan, 2017)
The research aims to improve the quality of studentâs content writing in biology through implementation of Project Based Learning model. The research is a Classroom Action Research (CAR) with the subjects of this research were students of class XI MIPA 6 SMA N 4 Surakarta are 32 learners. Research conducted by the cyclical phases: planning, implementation, observation, and reflection. The research data was collected through observation, documentation, and interviews, which are equipped with a writing rubric skills. Data validation method using triangulation techniques. Data were analyzed using qualitative descriptive analysis: reduction, presentation, and verification of data. The results showed an increase in the quality of learners writing the content for the application of the model Project Based Learning in learning biology.